Digestion and gut-microbiota fermentation of cocoa melanoidins: An in vitro study (2023)
ABSTRACT: This research aimed to compare the in vitro digestibility and fermentability of melanoidins extracted from cocoa nibs fast-roasted with a fluidized bed roaster (FR-melanoidins), melanoidins from cocoa nibs slow-roasted in a convective oven (SR-melanoidins), and native high molecular weight compounds extracted from unroasted cocoa nibs (UR-HMWC). Data showed that both types of melanoidin extracts, especially FR-melanoidins, better release polyphenols during digestion and earlier produce short-chain fatty acids during in vitro fermentation than URHMWC. The delayed catabolism of UR-HMWC resembled that of dense fibers, while FR- and SR-melanoidins resembled oligosaccharides. The production of SCFA was positively correlated with the increase in Bacteroides sp. The profile of the genera identified in the proximal colon showed the differences in fermentability between FR- and SR-melanoidins, with FR-melanoidins having the higher relative growth of nonpathogenic bacteria. This study demonstrated the in vitro digestibility of bound phenolic compounds and the potential prebiotic activity of cocoa melanoidins.